(untitled) (Mustansiria Dental Journal, 2024)
The effect of different phosphate- bonded investments on the marginal fitness of porcelain- fused—to-metal copings cast by one type of noble alloy and one type of base metal alloy was studied. Three types of phosphate—bonded investments (Castorit - Super C, Norvest, and Iraqivest) were used for investing the thirty copings of each group. The marginal fitness of each coping was determined by measuring the vertical marginal discrepancies between the gingival margin of the coping and the margin of the preparation at four reference points on the labial, mesial, palatal and distal aspects of the die by the aid of light traveling microscope . The statistical analysis of the results showed that there were significant differences in marginal fitness among different investments for both Pd- Ag& Ni-Cr alloys. The Castorit- Super C and Norvest investments produced comparable results with both alloys, while the Iraqivest appeared less compatible with Pd-Ag alloy than the other two investments and it had comparable compatibility to Norvest investment when used with Ni- Cr alloy. The Ni- Cr alloy (Heraenium NA) copings revealed significantly greater marginal discrepancy than the Pd-Ag alloy (QD) eopings specially when using Castorit- Super C and Norvest investments .